Felonious line-of-duty officer deaths (1995–2015): The impact of tenure and age revisited - Tucker-Gail, Kasey (International journal of police science & management, 2022)
The purpose of this article was to reassess patterns previously identified in the Federal Bureau of Investigation’s Law Enforcement Officers Killed and Assaulted (LEOKA) data, expanding the time frame from 5 years to 20 years, for application within law enforcement when considering training needs over the life cycle of an officer's career. Consistent with the findings of the earlier analysis, this study identifies two prevalent patterns: the age range with the highest frequency of death was 30–39, and the years of experience with the highest frequency of death was 0–4. In fact, the analysis indicates an even stronger pattern of the deadly combination of age and tenure. Implications of the study include the need for larger scale data collection on the national population of officers, detailed information on transfers and time of service overall (as opposed to time in service at current department), and evaluations of current training programs and practices regarding de-escalation and the use of force as well as self-defense and situational awareness.